Analysis of molecular aberrations of Wnt pathway gladiators in colorectal cancer in the Kashmiri population - Sameer A; Shah Zaffar A; Abdullah Safiya; Chowdri Nissar A; Siddiqi Mushtaq A (Human Genomics, 2011)
Abstract The development and progression of colorectal cancer (CRC) is a multi-step process, and the Wnt pathways with its two molecular gladiators adenomatous polyposis coli (APC) and β-catenin plays an important role in transforming a normal tissue into a malignant one. In this study, we aimed to investigate the role of aberrations in the APC and β-catenin genes in the pathogenesis of CRC in the Kashmir valley, and to correlate it with various clinicopathological variables. We examined the paired tumour and normal-tissue specimens of 86 CRC patients for the occurrence of aberrations in the mutation cluster region (MCR) of the APC gene and exon 3 of the β-catenin gene by polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) and/or PCR-direct sequencing. Analysis of promoter hypermethylation of the APC gene was also carried out using methylation-specific PCR (MS-PCR). The overall mutation rate of the MCR of the APC gene among 86 CRC cases was 12.8 per cent (11 of 86). Promoter hypermethylation of APC was observed in 54.65 per cent (47 of 86) of cases. Furthermore, we found a significant association between tumour location, tumour grade and node status and the methylation status of the APC gene (p ≤ 0.05). Although the number of mutations in the APC and β-catenin genes in our CRC cases was very low, the study confirms the role of epigenetic gene silencing of the pivotal molecular gladiator, APC, of the Wnt pathway in the development of CRC in the Kashmiri population.